Mapping analysis to predict the associated EuroQol five- dimension three- level utility values from the Oxford Knee Score. (2022) - Clement, N. D.; Afzal, I.; Peacock, C. J. H.; MacDonald, D.; Macpherson, G. J.; Patton, J. T.; Asopa, V.; Sochart, D. H.; Kader, D. F.
No abstract available